How to control the scaling of CaCO3: A "fingerprinting technique" to classify additives - Verch, A.; Gebauer, Denis; Antonietti, M.; Cölfen, H. (R S C Publications, 2011)
A titration set-up coupling ion selective electrodes with pH adjustment was used to analyze the effects of additives present during precipitation of calcium carbonate. Besides industrially well-established antiscalants (sodium triphosphate, citrate, polyacrylate and poly(aspartic acid)), also functional polymers being active in morphosynthesis (polystyrene sulfonate and poly(styrene-alt-maleic acid)) were analyzed. Interestingly each additive acts in its specific way, suggesting the notation "fingerprinting" for a complex interplay of up to five "solution modes" of influencing CaCO3 precipitation and crystallisation. The results provide new insights into the modes of additive controlled crystallisation, and in the long run, the insights may facilitate the design of precipitation systems that yield complex and tailor-made crystals. © 2011 The Owner Societies.